The Effect of Proposed Learning Program on Teaching Basic ‎Basketball Skills of Physical Education Majors at An-Najah ‎National University - Bader Dweekat; Subhi 'Isa (My University, 2005)
The purpose of this study was to investigate the effect of proposed learning program teaching basic Basketball skills of male physical education majors at (ANU). The sample of the study was consisted of (48) students, and they were divided equally for two groups first one as experimental group and the other as control group. The results reveled a positive effect of proposed learning program on teaching Basketball skills. Furthermore, the result indicated a significant differences between experimental and control groups in favor at experimental. Furthermore, the result revealed a significant development in some Skills for the control group. Based on the study findings the researchers recommended to applied the proposed learning program for different age groups for both male and female.

هدفت الدراسة التعرف إلى أثر برنامج تعليمي مقترح على تعلم بعض المهارات الأساسية السلة (1) لدى طلاب قسم التربية الرياضية، وقد شملت العينة على (48) طالباً، تم تقسيمها إلى مجموعتين متساويتين كل منهما (24) طالباً، قامت المجموعة الأولى الضابطة بالتعلم بالطرق التقليدية المتبعة بتدريس المساق، أما المجموعة الثانية التجريبية فقد طبق عليها البرنامج التعليمي المقترح ولمدة عشرة أسابيع. أظهرت النتائج أن مفردات البرنامج التعليمي المقترح أدت إلى تحسن فعال في جميع المهارات، كما أظهرت النتائج وجود فروق بين أفراد المجموعتين التجريبية والضابطة ولصالح التجريبية. كما وأظهرت النتائج أن المجموعة الضابطة أبدت بعض التحسن على بعض المهارات. وأوصى الباحثان على تطبيق البرنامج المقترح على فئات عمرية مختلفة ولكلا الجنسين.
أثر برنامج تعليمي مقترح على تعلم بعض المهارات الأساسية لكرة السلة